Estimation of hydraulic conductivity of porous media using data-driven techniques. Issue 12 (24th November 2022) - Thakur, Divya; Chandel, Abhishish; Shankar, Vijay
Abstract: Knowledge of hydraulic conductivity ( K ) is inevitable for sub-surface flow and aquifer studies. Hydrologists and groundwater researchers are employing data-driven techniques to indirectly evaluate K using porous media characteristics as an alternative to direct measurement. The study examines the ability of the Adaptive Neuro-Fuzzy Inference System (ANFIS) to predict the K of porous media using two membership functions (MFs), i.e., triangular and Gaussian, and support vector machine (SVM) via four kernel functions, i.e., linear, quadratic, cubic, and Gaussian. The techniques used easily measurable parameters namely effective and mean grain size, uniformity coefficient, and porosity as input variables. A 70 and 30% dataset is used for the training and testing of models, respectively. The correlation coefficient ( R ) and root mean square error (RMSE) were used to evaluate the models. The Gaussian MF-based ANFIS model outperformed the triangular model having R and RMSE values of 0.9661 & 0.0010 and 0.9532 & 0.0015, respectively, whereas the quadratic kernel-based SVM model with R and RMSE values of 0.9520 and 0.0015 performs better than the other SVM models. Based on the evaluation of ANFIS and SVM models, the study establishes the efficacy of the Gaussian MF-based ANFIS model in estimating the K of porous media. HIGHLIGHTS: The study focuses to develop a hydraulic conductivity model based on easily measurable grain-size parameters using the two data-driven techniques, i.e., ANFIS and support vector machine. The data-driven approaches result in the quick estimation of hydraulic conductivity, which is useful in determining the groundwater recharge with precise accuracy. Graphical Abstract